2022
DOI: 10.3390/foods11040538
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization, Antibacterial Activity, and Embryo Acute Toxicity of Rhus coriaria L. Genotype from Sicily (Italy)

Abstract: This study reports a full characterization of the Sicilian sumac, Rhus coriaria L. This fruit represents a potential source of fiber (33.21 ± 1.02%) and unsaturated fatty acids, being the contents of linoleic and α-linolenic acids, 30.82 ± 1.21% and 1.85 ± 0.07%, respectively. In addition, the content of phenolic and total anthocyanin was 71.69 ± 1.23 mg/g as gallic acid equivalents, and 6.71 ± 0.12 mg/g as cyanidin-3-O-glucoside equivalents, respectively. The high content in mineral elements, consisting mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…rapa DC.) [23]; Crinum angustum [110]; Tinospora cordifolia and Alstonia scholaris [111]; Rhus coriaria L. [112]; Calycotome villosa [78];…”
Section: Klebsiella Pneumoniae 16mentioning
confidence: 99%
“…rapa DC.) [23]; Crinum angustum [110]; Tinospora cordifolia and Alstonia scholaris [111]; Rhus coriaria L. [112]; Calycotome villosa [78];…”
Section: Klebsiella Pneumoniae 16mentioning
confidence: 99%
“…The principally identified flavonoids of methanol/aqueous extracts in Sicilian Sumac are quercetin 3-O-galactoside, kaempferol 3-O-glucoside, quercetin, and myricetin 3-O-hexoside. Among the organic acids, the main representatives are gallic acids and pentagalloyl-hexoside [ 11 ]. The volatile compounds of Sicilian Sumac determine the composition of essential oils and are prevalently derived from monoterpenoids and sesquiterpenes such as β-caryophyllene and α-pyrene, respectively, and from non-terpenes compounds such as aldehydes [ 7 , 12 ].…”
Section: Sumac and Sumac Extracts Compositionmentioning
confidence: 99%
“…Furthermore, fibers and unsaturated fatty acids, such as palmitic acid, linolenic and α-linoleic acids (omega-3 and -6), can be found. Potassium, calcium, magnesium, and phosphorus are the major mineral components in Sicilian Sumac [ 11 ]. Exhaustive information about the composition in vitamins is lacking, although some scientific works analyzing Syrian Sumac water extracts described a main content of pyridoxine, ascorbic acid, thiamine, and riboflavin [ 5 , 13 ].…”
Section: Sumac and Sumac Extracts Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show the safety of the tested spices, which is an important step for their safe use. Lo Vecchio et al [ 4 ] reported the full characterization of Rhus coriaria L., a fruit from Sicily which is a potential source of fiber (33.21 ± 1.02%) and unsaturated fatty acids and linoleic and α-linolenic acids (30.82 ± 1.21% and 1.85 ± 0.07%, respectively). Along with the high content in phenolic, anthocyanin, and minerals, its non-toxicity has been confirmed through tests of its extract on zebrafish embryos.…”
mentioning
confidence: 99%